Practical Guide to Corporate Governance : Experiences from the Latin American Companies Circle - International Finance Corporation; OECD (International Finance Corporation, Washington, D.C., 2017)
This publication details 14 firms recognized for better corporate governance practices that had suffered less damage than average listed Latin American companies during the finanicial crisis. It offers an opportunity for business leaders in Latin America to learn from the experience of peers who have successfully implemented substantive improvements in governance standards and practices. Although the guide has been in the works for several years, the timing of its publication coincides with a global financial crisis that has catapulted corporate governance to a top spot on the global policy agenda. With gaps in governance from inadequate risk management to distorted incentives structures factoring in as contributing to the crisis, good corporate governance practices will be an important part of the response needed for Latin American economies, as well for others around the world. Within this context, there has been a remarkable growth in awareness and activity surrounding corporate governance during the last decade, as recognized by the Latin American roundtable on corporate governance. This is an ongoing initiative of the Organization for Economic Co-operation and Development and the International Finance Corporation/World Bank Group that has brought together policy-makers, regulators, stock exchanges, investors, companies and other stakeholders on an annual basis to promote improved policies and practices specific to the Latin American context. This practical guide is an outgrowth of these efforts, involving many steps along the way. When members of the Roundtable called for greater participation from private sector companies in the Roundtable's corporate governance improvement efforts, the companies circle was born. A first book of case studies was launched in 2005, with an expanded second edition issued in 2006. Members of the circle were keen to share experiences and believed a wider audience of Latin businesspeople will benefit from a practical guide exploring the ways and whys of their governance improvements.